Economic development of the Russian manufacturing industry under sanctions - S. Ye. Afonin (Вестник университета)
The article presents a study to assess main indicators of efficiency of production process development in the manufacturing industry of the Russian Federation in recent years, related to the negative impact of the COVID-19 pandemic on industrial production and on manufacturing in general. The purpose of the study is to examine the level of manufacturing industrial production development in the Russian Federation under the conditions of sanctions. To achieve this goal, international and domestic experience of manufacturing industry economic development has been studied, which in general terms characterizes the level of competencies required for manufacturing industries effective development. A comparative assessment of such approaches has been carried out. The study used the summary and grouping methods, tabular and graphical methods of information presentation, dynamics analysis methods. The information base of the study was microdata of sample surveys of the Federal State Statistics Service. The indicators have been presented in annual periodicity for 2016–2022 for Russia. As a result of studying economic development of manufacturing industry types, their pros and cons have been established. On the basis of statistical data and sample surveys for 2022, their systematization and evaluation have been carried out. The changes that occurred in main economic indicators characterizing the manufacturing industry sphere development have been studied. The study pays attention to the indicators characterizing industry development in Russia. The article concludes that in the future it will be necessary to continue the manufacturing industry transformation on an innovative basis.